(untitled) - Logan, Daryl L. (Boston, 1986)
Provides a simple, basic approach to the finite element method that can be understood by both undergraduate and graduate students. It does not have the usual prerequisites (such as structural analysis) required by most available texts in this area
Keywords: Phương pháp phần tử hữu hạn,Finite element method